DEVELOPING STUDENTS’ ARTISTIC THINKING THROUGH MATERIAL WORK IN SCULPTURE EDUCATION - Qurbonova Sitora Yunus qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores how working with various materials in sculpture education can enhance students’ artistic thinking. The study emphasizes the pedagogical value of using traditional materials such as clay, wood, and gypsum, along with modern materials like polymer and plastic, to stimulate creativity, critical thinking, and imaginative problem-solving. By engaging with different materials, students develop practical skills, aesthetic judgment, and the ability to integrate technical knowledge with creative expression.